Multi-criteria optimization of Brewing technological processes - Romanov, Mykola (My University, 2016)
When setting a problem of optimal control one of the main issues is the choice of optimality criterion. Development of algorithms of brewing process multi-criteria control based on criteria situational priority and fuzzy limits will increase technological complex productivity and the quality of the finished product.
Keywords: виробництво пива; багатокритеріальна оптимізація; производство пива; многокритериальная оптимизация; beer production; multi-criteria optimization; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка